Effect of inhaled endotoxin on induced sputum in normal, atopic, and atopic asthmatic subjects - Nightingale, J. (BMJ Group, 1998)
BACKGROUND—Inhalation of lipopolysaccharide (LPS) causes an inflammatory response in the lungs. To explore this response, inflammatory indices were measured in induced sputum from atopic asthmatic patients and compared with atopic and non-atopic subjects after inhalation of LPS. METHODS—The effects of inhaled LPS (60 µg) or placebo (0.9% saline) were examined in a randomised, double blind, crossover trial in 11 non-atopic normal subjects, seven atopic, non-asthmatic individuals, and eight atopic, asthmatic patients. Sputum was induced by inhalation of 3.5% saline before the test inhalation and again at six hours and 24 hours. Spirometry (forced expiratory volume in one second (FEV(1)), forced vital capacity (FVC)), heart rate, blood pressure, and temperature were recorded before challenge and at intervals until eight hours, and at 24 hours after challenge. RESULTS—There was no change in cardiovascular parameters or spirometry with either exposure in any group. In the asthmatic patients only, inhalation of LPS caused a rise in temperature, with a peak of 0.6°C at seven hours, which was significantly higher than following placebo inhalation (p<0.05). In normal subjects, LPS caused a significant rise in absolute neutrophil counts at 24 hours compared with placebo (median 1.1 × 10(6) cells/ml after LPS; median 0.2 × 10(6) cells/ml after placebo, p<0.01), but no change in differential counts. In asthmatic patients, LPS caused a significant rise in differential neutrophil counts at six hours compared with placebo (median 88% after LPS; median 56% after placebo, p<0.05), but no change in absolute cell counts at any time point. There was no change in neutrophil counts in the atopic subjects. There was a significant rise in sputum interleukin 8 (IL-8) concentrations in normal subjects at six hours compared with placebo (mean placebo 1.1 ng/ml; LPS 3.0 ng/ml, p<0.05) and in asthmatics at 24 hours (mean placebo 2.0 ng/ml, LPS 6.9 ng/ml, p<0.05). There were no changes in sputum concentrations of tumour necrosis factor α or granulocyte macrophage colony stimulating factor at any time. CONCLUSIONS—Inhalation of LPS causes a neutrophilic inflammation with increases in IL-8 in both normal and asthmatic subjects.